2015
DOI: 10.1002/path.4674
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end‐products induce skeletal muscle atrophy and dysfunction in diabetic mice via a RAGE‐mediated, AMPK‐down‐regulated, Akt pathway

Abstract: Diabetic myopathy, a less studied complication of diabetes, exhibits the clinical observations characterized by a less muscle mass, muscle weakness and a reduced physical functional capacity. Accumulation of advanced glycation end-products (AGEs), known to play a role in diabetic complications, has been identified in ageing human skeletal muscles. However, the role of AGEs in diabetic myopathy remains unclear. Here, we investigated the effects of AGEs on myogenic differentiation and muscle atrophy in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 49 publications
7
141
1
1
Order By: Relevance
“…Histological examination was assessed by using haematoxylin and eosin staining. For assessment of the collagen deposition during muscle regeneration, the paraffin‐embedded soleus muscle sections were stained with Masson's trichrome as described previously . Immunohistochemistry was performed on fixed soleus muscle sections for Atrogin‐1 and SIRT‐3 staining with anti‐mouse Atrogin‐1 rabbit polyclonal antibody and anti‐mouse SIRT‐3 rabbit polyclonal antibody (Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological examination was assessed by using haematoxylin and eosin staining. For assessment of the collagen deposition during muscle regeneration, the paraffin‐embedded soleus muscle sections were stained with Masson's trichrome as described previously . Immunohistochemistry was performed on fixed soleus muscle sections for Atrogin‐1 and SIRT‐3 staining with anti‐mouse Atrogin‐1 rabbit polyclonal antibody and anti‐mouse SIRT‐3 rabbit polyclonal antibody (Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Human tissue sampling of the present study was reviewed and approved by the National Taiwan University Hospital Institutional Review Board for clinical investigation and collected after written informed consent from all participating subjects. The process of isolation and culture of primary HSMPCs was described previously . Briefly, human skeletal muscle biopsies (~0.2 g) were collected from 10 rectus muscles of patients under orthopaedic surgery (mean age, 64 years; range, 34 to 81 years, both male and female).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Muscle atrophy is length dependent with more distal muscle areas showing greater losses. 34 Skeletal muscle atrophy may be related to increased advanced glycation end products and receptors 55 or reduced insulin signaling in skeletal muscle. 56 Adipose tissue in the muscle is increased in DPN, in particular in the posterior leg.…”
Section: The Effects Of Dpn On Skeletal Muscle Functionmentioning
confidence: 99%
“…Khalil et al demonstrated that this manifests as through significant weight loss, muscle mass atrophy and increased rate of degradation of contractile proteins . In relation specifically to skeletal muscle, this atrophy is accompanied by pronounced muscular weakness and physical incapacity .…”
Section: Introductionmentioning
confidence: 99%